Sosialisasi Produk Berbahan Baku Komoditas Pisang Unggulan Industri Rumah Tangga Bagi Masyarakat Di Desa Selotong - Abdillah; Afifa Yasmin Zahira2; Nova Tri Indah Br.Rambe3; Nurmisda Ramayani (peduli riset dan pengabdian masyarakat, 2024)
The average banana production yield in Selotong Village is 6.2 tons/year. Most of the bananas produced in Selotong Village are sold unprocessed to buyers. Only a few farmers process it into ordinary original banana chips, so there is still a lack of human resources and a lack of innovation in processing these bananas. In this community service activity, material is developed in two aspects, namely the production aspect and the management aspect. The production aspect is to improve the ability of human resources to produce products to provide quality results, while the management aspect is to improve their skills in the areas of business management, production management, marketing management, simple financial management and capital. The objectives of this activity are (1) Providing technical knowledge to the community regarding processing bananas into value-added products, (2) Developing community skills and abilities related to home industry, such as banana processing techniques, small business management, and marketing strategies ( 3) Provide an understanding of the importance of product quality, branding and marketing strategies to increase the competitiveness of banana products from Selotong Village in local and regional markets. The resulting outputs are (1) products made from superior bananas which are innovative and high quality, (2) skilled human resources, (3) correct business management and financial administration.